2021
DOI: 10.21037/atm-21-649
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expressions of spinal cord injury treated by neurotropin and nafamostat mesylate

Abstract: Background: Spinal cord injury (SCI) leads to severe physical disability and sensory dysfunction. Neurotropin (NTP) has been used clinically to alleviate neuropathic pain, while nafamostat mesylate (NM) used clinical on pancreatitis patients through inhibiting synthetic serine protease. Our previous studies showed that NTP and NM were able to repair SCI. However, the underlying mechanism has not been fully explored after treatment with these 2 different drugs. Methods:The drugs NTP and NM were administered on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…In our previous study, the result of in ammation chip sequencing showed that NM could reduce many chemokines expression in local site of SCI [34]. Here, we also proved that administration of NM after SCI reduced neutrophil and macrophage in ltration signi cantly, which we believed that the protection of BSCB was a considerable mechanism of the anti-neuroin ammation effect induced by NM.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In our previous study, the result of in ammation chip sequencing showed that NM could reduce many chemokines expression in local site of SCI [34]. Here, we also proved that administration of NM after SCI reduced neutrophil and macrophage in ltration signi cantly, which we believed that the protection of BSCB was a considerable mechanism of the anti-neuroin ammation effect induced by NM.…”
Section: Discussionsupporting
confidence: 65%
“…There is an expanded effect in other diseases, such as COVID-19 [33]. We have previously reported that NM has bene cial effect on SCI [34,35]. However, its administration time window and speci c mechanism remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NM inhibits lipopolysaccharide‐induced nitric oxide production, apoptosis, and interleukins 6 and 8 levels in cultured human trophoblasts. NM has also antioxidant effects in TNF‐α‐induced ROS production 2, 17 and a neuroprotective role during ischemia‐induced brain or spinal cord injury has also been suggested 18,42 . The cross‐talk between coagulation and inflammation is, indeed, a key issue of the interaction between patients' blood and the external surfaces and circuit, which fuels a detrimental vicious circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Nafamostat is an FDA-approved drug to treat pancreatitis and is being explored as a treatment for other diseases, such as COVID-19 [ 35 ]. We have previously reported that nafamostat has a beneficial effect on recovery from SCI [ 9 , 36 ]. However, its administration time window and specific mechanism were unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the result of inflammation ChIP sequencing showed that nafamostat could reduce many chemokines expression in local site of SCI [ 36 ]. Here, we also proved that administration of nafamostat after SCI reduced neutrophil and macrophage infiltration significantly, which we believed that the protection of BSCB was a considerable mechanism of the anti-neuroinflammation effect induced by nafamostat.…”
Section: Discussionmentioning
confidence: 99%